2020
DOI: 10.2106/jbjs.19.01169
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Performance of Bone-Anchored Prostheses in Persons with a Transfemoral Amputation

Abstract: Background: For almost 30 years, bone-anchored prostheses have offered an alternative solution to prosthetic sockets by attaching the artificial limb directly to the femoral residuum by means of an osseointegration implant. Osseointegration implant surgery was introduced in our center in 2009. The aim of the present study is to report on safety, prosthesis-wearing time, and health-related quality-of-life (HRQoL) for patients with femoral bone-anchored prostheses during a 5-year follow-up period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 27 publications
3
66
0
6
Order By: Relevance
“…In the 5-year follow-up of the 51 patients with OPRA implants, 70 superinfections occurred in 34 patients (67%) and 14 deep infections occurred in 11 patients (22%) ( Branemark et al, 2019 ). The results are similar to the 5-years retrospective study on 39 patients using the press-fit implants, in which thirty patients (77%) presented with 156 events of superficial infections in total, with eight events (5%) in 4 patients being classified as deep infections ( Reetz et al, 2020 ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the 5-year follow-up of the 51 patients with OPRA implants, 70 superinfections occurred in 34 patients (67%) and 14 deep infections occurred in 11 patients (22%) ( Branemark et al, 2019 ). The results are similar to the 5-years retrospective study on 39 patients using the press-fit implants, in which thirty patients (77%) presented with 156 events of superficial infections in total, with eight events (5%) in 4 patients being classified as deep infections ( Reetz et al, 2020 ).…”
Section: Introductionsupporting
confidence: 85%
“…In the OPRA cohort, the abutment and/or abutment screw fractures occurred in 15 of the 51 patients (29%) within 5 years ( Branemark et al, 2019 ). Among the 39 patients using the ILP system, nine patients (23%) got 12 dual-adaptor breakages in 5 years ( Reetz et al, 2020 ). A long-term follow-up of 111 patients using the OPRA system indicates that mechanical complications dramatically increased after 8 years of OPRA usage.…”
Section: Introductionmentioning
confidence: 99%
“…Taking a closer look, what they really reported was one deep infection (2%), six fractures of (generally smaller-diameter) intramedullary stems (10%), and 13 broken transcutaneous dual cone adapters (22%). Earlier reports from these authors and others [1,12], including many of the same patients at earlier time points, reported a lower frequency of mechanical problems (as might be expected with shorter follow-up) and frequent minor soft tissue infections but demonstrated improved prosthesis use and health-related quality of life. The stem fracture rates are higher than might be expected or hoped for, and the authors attribute this to smaller diameter stems and an increased number of infectious events.…”
supporting
confidence: 55%
“…9 Today, bone-anchored prostheses (BAPs), directly attached to a percutaneous implant, have become an alternative to socketsuspended prostheses (SSPs), especially in patients who have undergone transfemoral amputation (TFA) for reasons other than vascular disease and who have difficulty obtaining adequate and comfortable socket suspension. [10][11][12][13] Among patients using BAPs, improvements in patient-reported outcomes with regard to prosthetic function and HRQL have been reported as compared to their previous situation, [14][15][16][17][18] although in conjunction with implantrelated complications. 14,[17][18][19][20][21] Health economic evaluations of BAPs have shown higher costs, fewer visits, and some gain of qualityadjusted life-years (QALYs) as measured by the use of SF-36/SF-6D and as compared to the SSPs.…”
Section: Introductionmentioning
confidence: 99%